REKONSEPTUALISASI PENGADILAN PERTANAHAN - Simanjuntak, Enrico (Jurnal Hukum dan Peradilan, 2014)
There are at least three basic argument behind the idea of settlement of the special land dispute court, namely : first, the recognizing of the land bill drafter of the complexity of the land disputes. Second, the idea of settlement of special land dispute court is intended to restore the previous special court (Landreform Court) in the sixties era. Three, the special land dispute court of land is basically intended to repair the malfuncion of present court in settlement of the land disputes. But the academic draft and bill of land rises some questions about the know-how land disputes of the bill’s drafter, it proposes that this academic draft and bill of land does not take a sufficiently deep assessment. The author assumes that the flaws of academic draft is relating to the lack of legal problem mapping in land disputes, including the basic knowledge of legal system in land disputes. This situation reflects the banality of data and legal situation analysis which affects the misconception of the elemental interconection of legal normative with the structure of social aspect by jumpling to conclusion and forced conclusion. Finally, some solution which is proposed in this bill of land is diametrically opposed with the basic need of agrarian reforms and judicial empowerment project, especially administrative court. Keywords: Bill of land, Land Court, Administrative Court